Decomposing Fertility Differences Across World Regions and Over Time: Is Improved Health More Important than Women's Schooling? - Suzanne Duryea; Jere R. Behrman; Miguel Székely (Inter-American Development Bank, Office of the Chief Economist, 1999)
There is a recent renewal of interest in the relation between shifts in age structures of populations and various economic outcomes. These shifts are triggered by changes in fertility and mortality that take place some years before becoming apparent in the standard age structure and that may create windows of opportunity for subsequent development. A large number of countries in the world are still experiencing, or probably about to experience, fertility declines. This paper first characterizes differences in fertility and mortality and in related dependency ratios across regions and over time. The paper then uses a panel of 96 countries covering the period 1965-1995 to decompose the differences in fertility rates between developed and developing countries and the differences in fertility between 1960 and 1995 for several developing regions and for 22 individual countries in the Latin American and Caribbean region. These decompositions indicate that the main correlates of fertility differences across space and over time are female schooling and health, with the former having larger associations with differential fertility among regions/countries at a point of time and the latter having larger associations with fertility declines over time. This suggests that the importance of associations of increased female schooling relative to those of improved health may be overstated in the literature, which is substantially based on inferring longitudinal relations from cross-sectional data.
Keywords: 330; Fertilität; Frauenbildung; Gesundheitsvorsorge; Bevölkerungsstruktur; Welt